Consistent condom use and its associated factors among human immunodeficiency virus-positive pregnant women in Ethiopia - Tibebu, Nebiyu Solomon; Kassie, Belayneh Ayanaw; Kebede, Azmeraw Ambachew; Anteneh, Tazeb Alemu; Temesgan, Wubedle Zelalem; Aklil, Mastewal Belayneh; Wondie, Kindu Yinges; Abegaz, Marta Yimam; Ayalew, Hiwotie Getaneh; Rade, Bayew Kelkay (Frontiers in Medicine, 2022)
Background: Consistent condom use plays a significant role in the successful protection of the transmission of human immunodeficiency virus (HIV) infection in couples with sero-discordant HIV status, mother-to-child-transmission (MTCT), and acquiring other strains in HIV positive concordant pairs. Limited data and information about this issue in low-resource setting countries, including the study setting. Therefore, this study aimed to assess the level of consistent condom use and its associated factors among pregnant women living with HIV HIV-positive. Methods: An institution-based cross-sectional study was done from October 17, 2020, to March 1st, 2021. A total of 423 HIV-positive pregnant women were involved in this study and selected using a systematic random sampling technique. Data were collected using a semi-structured, pretested, and interviewer-administered questionnaire then entered to EPI INFO version 7 and analyzed using SPSS (Statistical Package for Social Sciences) version 21. Logistic regressions were performed to identify factors. P-value ≤ 0.05 was the cutoff point to declare statistical significance. Results: The prevalence of consistent condom utilization among HIV positive pregnant women was 14.2% (95 % CI (Confidence Interval): 10.9%, 17.5%). Women having higher educational status (AOR = 6.33, (95% CI, 1.96, 20.42), women having CD4 count greater than 600cells/mm (AOR = 4.78, 95% CI: 2.08, 10.97), tested positive for HIV during non-pregnant state (AOR = 5.99, 95% CI: 3.01, 11.94), and disclosing their HIV status to sexual partners (AOR = 4.85, 95% CI: 1.71, 13.71) were found to be statically significant with women’s consistent condom utilization. Conclusion: In this study, consistent condom uses among pregnant women living with HIV was low. Women having educational status of college and above, tested positive for HIV during non-pregnant state, disclosing their HIV status to a sexual partner, and having CD4 count greater than 600 cell/mm had better consistent condom utilization. Hence, giving more emphasis on health education and counseling service about HIV testing before pregnancy and disclosing their HIV status to their sexual partners, and about the need for consistent condom use during pregnancy would be important.